Penerapan Model Pembelajaran Course Review Horay Untuk Meningkatkan Hasil Belajar Membaca Narasi Siswa Kelas V - Halik, Abdul; Usman; Fatwa S, Aco Putra Rezky M (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The problem in this study is the low learning outcomes of class V UPTD SD Negeri 77 Barru Barru Regency. The results of this study is an increase in student learning processes and outcomes. In cycle I the results of teacher observations were in the good category (B) and the results of student observations were in the sufficient category (C). In cycle II the results of teacher observations were in the good category (B) and the results of student observations were in the sufficient category (C). Whereas in cycle III the teacher's observation results were in the good category (B), for the student observation results were in the good category (B). While in the third cycle of student learning outcomes showed completeness of 87.5% in the good category. The conclusion in this study is that by applying the type cooperative learning modelCourse Review Horay (CRH) can improve the process and results of learning to read comprehension of narratives for class V UPTD SD Negeri 77 Barru Barru Regency.